Evaluating the antioxidant and antimicrobial activities of corn (Amylum maydis) starch-based edible coating with the addition of honey mango (Mangifera indica L.) leaf extract and liquid smoke - Nur Sholihah, Laila Melati; Satar, Ibdal (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Edible coatings represent one of newest innovations to protect wet food products from chemical and microbial damages. However, these coatings are low (or zero) antioxidant and antimicrobial activities. Honey mango leaf extract (HMLE) and liquid smoke (LS) are two additives that can be added into edible coatings to improve their antioxidant and antimicrobial properties. In addition, corn starch (CS) was used as a main ingredient to provide the edible coating with desirable physical property. This study investigated the antioxidant and antimicrobial activities of corn starch-based edible coatings with the addition of HMLE and LS. Six formulations were prepared with varying HMLE and LS ratios of 0:0 (F0), 0:6 (F1), 2:4 (F2), 3:3 (F3), 4:2 (F4), and 6:0 (F5). The antioxidant activity (IC50) was evaluated using the DPPH method, and antimicrobial activity was assessed by total plate count (TPC) methods. All data were statistically analyzed using one-way ANOVA at a significance level of 0.05. The IC50 values of all edible coatings ranged from 44.55 to 304.94 ppm. Meanwhile, the TPC values of all edible coatings were observed to be less than 1 × 105 cfu/g (or not detected, ND), demonstrating effective antimicrobial activity. Based on both the IC50 and TPC values, formulation F4 emerged as the best formulation. Overall, these results indicated that the incoorporation of HMLE and LS significantly increased the antioxidant and antimicrobial activity of edible coatings.